To calculate the average rate of change of the function \( f(x) = x^2 + 6x + 8 \) over the interval \([-2, 0]\), we will apply the formula:
\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]
Here, \( a = -2 \) and \( b = 0 \).
- We need to find \( f(-2) \) and \( f(0) \):
From the provided function table:
- \( f(-2) = 0 \)
- \( f(0) = 8 \)
- Now we can substitute these values into the average rate of change formula:
\[ \text{Average Rate of Change} = \frac{f(0) - f(-2)}{0 - (-2)} = \frac{8 - 0}{0 + 2} = \frac{8}{2} = 4 \]
Thus, the average rate of change of the function \( f(x) \) over the interval \([-2, 0]\) is \(\boxed{4}\).